Pengaruh foot hydrotherapy daun pandan (Pandanus amaryllifolius) terhadap insomnia pada remaja - Ni Made Larasati; Ni Rai Sintya Agustini; Yohanes Zenriano Tarigan (Jurnal Teknologi Kesehatan (Journal of Health Technology), 2026)
Insomnia is a sleep disorder characterized by difficulty initiating or maintaining sleep despite adequate opportunity to rest, which can lead to impaired daytime functioning, fatigue, frequent nocturnal awakenings, and long-term health risks such as cardiovascular disease, metabolic disorders, cognitive decline, and increased mortality risk. Adolescents are particularly vulnerable to insomnia due to sleep needs of approximately 8–10 hours per night, which are often not fulfilled because of academic demands and social activities. Non-pharmacological interventions, such as foot hydrotherapy using pandan leaves (Pandanus amaryllifolius), are proposed as an alternative approach to improve sleep quality. This study aimed to determine the effect of foot hydrotherapy using pandan leaves on insomnia among adolescents at SMPN 1 Negara. The study used a quantitative approach with a one-group pretest–posttest design. The population consisted of 93 adolescents experiencing insomnia, with samples selected using convenience sampling. Data were collected using a demographic questionnaire and the Jakarta Insomnia Rating Scale (KSPBJ-IRS). Data analysis was performed using the Wilcoxon Signed Rank Test. The results showed a significant difference between pretest and posttest scores with a p-value < 0.001, indicating a reduction in insomnia levels after the intervention. In conclusion, foot hydrotherapy using pandan leaves has a significant effect in reducing insomnia among adolescents.